Diagnosis and Treatment of a Forearm Glomangioma: A Case Study - Ethan Kosco; Maya Mendonsa; Dalton Blood; Martin Skie (Journal of Orthopaedic Case Reports)
Introduction: Glomangiomas are rare vascular tumors derived from the vascular component of glomus bodies. Because glomus bodies play an important role in thermoregulation in the digits of the hand and foot, glomus tumors predominantly arise in these locations. Only six incidents of glomangiomas have arisen in the forearm since 1991. In nearly every case, the tumor was associated with extreme tenderness to palpation and pain with the use of the forearm. The diagnosis was delayed up to 21 years due to the low clinical suspicion of this type of tumor. However, eventual diagnosis and surgical management led to immediate resolution of pain in the forearm. Case Report: We report the diagnosis and treatment of a 52-year-old male who presented with a 5-year history of volar mid-forearm pain refractory to conservative treatment. Diagnostic evaluation with magnetic resonance imaging and histology identified the tumor as a glomangioma. Conclusion: Surgical excision completely resolved the patient’s symptoms by the 2-week follow-up.